Pengaruh Komentar Netizen Terhadap Kesehatan Mental Orang Tua Anak Berkebutuhan Khusus - Erika Nauli Sibarani; Lenggang Nalaswari; Muhammad Ihya Ulumuddin H; Yulia Hana Nurlatifah; Siti Hamidah (Pusat Riset dan Inovasi Nasional, 2023)
This article reviews the influence of netizen comments on the mental health of parents of children with special needs. The research analyzed in the article is based on the background of the problem that negative comments have a significant impact on the mental health of parents with disabilities, so this research aims to address the stigmatization and discrimination of persons with disabilities and their families on social media and encourage people to treat them with the same respect and understanding as other people. This type of research is qualitative research with a naturalistic paradigm. The method used in the assignment article for the Indonesian Language Education course is a systematic literature review (SLR). The research instrument is a survey and the researcher is the key instrument. The data source for this research is the results of a survey of several comments on the social media accounts of parents of children with special needs. The result is making learning media in the form of posters or videos, and others about the effect of bad comments on the mental health of parents of children with special needs as well as the importance of being responsible and being wise in writing comments on social media.